The sensitivity and specificity of neutrophil lymphocyte count ratio in diagnosing sepsis patients at Dr. Saiful Anwar General Hospital, Malang, Indonesia - Agustin Iskandar; Yeni Ayu Prihastuti; Muhammad Anshory (Intisari Sains Medis, 2019)
Background: Sepsis is the most severe manifestation of acute infection which can cause death in 30-50% of cases. Rapid and accurate diagnosis of sepsis is a challenge for clinicians and laboratories. Neutrophil Lymphocyte Count Ratio is a potential index to detect the occurrence of sepsis. This examination is easy, fast and cheap. Procalcitonin is currently widely used as a newer indicator in diagnosing pre-shock but is rarely done because of its cost. This study aims to compare the diagnostic value of Neutrophil Lymphocyte Count Ratio with procalcitonin as a marker in septicpatients.Method: A Case-control analytic research was conducted from March to June 2018. Examination of neutrophils and lymphocytes using Sysmex XN-1000 while procalcitonin examination used Elecsys BRAHMS PCT using ECLIA method. Diagnostic values are analyzed using the ROC curve, and the cut-off value is determined. The sensitivity, specificity, positive predictive value, negative predictive value, accuracy are calculated with 2x2 tables.Result: The subjects of the study were 60 patients who hospitalized and examined for procalcitonin with 30 patients diagnosed based on clinical symptoms and SOFA score â‰¥ two by clinicians as sepsis patients and also 30 control patients. ROC analysis with procalcitonin cut-off values of 2,24 ng / mL obtained a sensitivity of 93%, specificity of 86,7%, PPV of 86,9%, and NPV of 92,4%.. At the cut-off value of Neutrophil Lymphocyte Count Ratio 5,06, there was a sensitivity of 80%, specificity of 76,7%, PPV of 76,9%, and NPV of 79,1%.Conclusion: Procalcitonin has a better diagnostic value than Neutrophil Lymphocyte Count Ratio in diagnosing sepsis.